2021
DOI: 10.37506/ijfmt.v15i1.13483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workstation Exercise and Ergonomic Exercise on Nursing Population – A Randomized Clinical Trial Research Protocol

Abstract: BackgroundNursing workers represent a significant proportion of the hospital workforce. In recent times, focus is put on increasing efficacy with reducing the concurrent risks in this population. Many researches imply on including workplace modifications and various exercises to reduce the number of absenteeism and heighten the quality in work. As low back ache is the most prevalent, this study targets on determining the effects of workstation exercise and ergonomic intervention on it.Purpose -Nursing staff is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Our results also found several high-impact articles that employed the quasi-experimental method to compare the control group with the main group or other relevant groups (Dhole et al, 2021;Esmaeili et al, 2023;Heidarimoghadam et al, 2020;Hijam et al, 2020;Lin et al, 2022;Mohammad Yusof et al, 2021;Motamedzadeh et al, 2021;So et al, 2019;Yang et al, 2021). Such an approach allows for a rigorous examination of the effects of interventions and facilitates a comprehensive analysis of the research findings.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Our results also found several high-impact articles that employed the quasi-experimental method to compare the control group with the main group or other relevant groups (Dhole et al, 2021;Esmaeili et al, 2023;Heidarimoghadam et al, 2020;Hijam et al, 2020;Lin et al, 2022;Mohammad Yusof et al, 2021;Motamedzadeh et al, 2021;So et al, 2019;Yang et al, 2021). Such an approach allows for a rigorous examination of the effects of interventions and facilitates a comprehensive analysis of the research findings.…”
Section: Discussionmentioning
confidence: 53%
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation